2018
DOI: 10.1002/cctc.201701673
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copper Loading on Iron Carbide Formation and Surface Species in Iron‐Based Fischer–Tropsch Synthesis Catalysts

Abstract: The effect of copper as promoter on iron carbide formation and the nature of surface species on iron‐based catalyst during Fischer–Tropsch synthesis (FTS) was investigated. Iron‐based catalysts (15 wt % of Fe) supported on alumina promoted with copper (0, 0.6, 2, and 5 wt %) were characterised in situ at relevant FTS conditions. The catalysts promoted with 2 and 5 wt % of Cu showed higher catalytic activity due to the formation of Hägg carbide (Fe5C2) detected by in situ XANES and XRD. The carbide formation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 102 publications
(355 reference statements)
2
18
0
Order By: Relevance
“…Numerous studies have shown [7,27,50] that the addition of copper can result in an enhancement of the activity of Fe-based FT catalysts. The major copper function is to decrease the temperature required for the reduction of iron oxides, while the reports about the effect of copper on the selectivity are still controversial.…”
Section: Mobile Promoters For Iron Ft Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown [7,27,50] that the addition of copper can result in an enhancement of the activity of Fe-based FT catalysts. The major copper function is to decrease the temperature required for the reduction of iron oxides, while the reports about the effect of copper on the selectivity are still controversial.…”
Section: Mobile Promoters For Iron Ft Catalystsmentioning
confidence: 99%
“…Several elements have been considered previously for promotion of iron catalysts. Most of earlier publications have been focused on the promotion of iron catalysts with alkali metals [6,[19][20][21][22][23][24][25] and copper [6,24,26,27]. More recently, the group of de Jong [28][29][30] and Sasol researchers [31] reported that simultaneous addition of sodium and sulfur improves selectivity to olefins in their synthesis from syngas over iron catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, iron catalysts for FT synthesis contain [1] several components. Iron catalysts are most frequently promoted with copper [17][18][19][20][21][22]. Copper has very low solubility in metallic iron (2.7 at.…”
Section: Introductionmentioning
confidence: 99%
“…It is a challenge to make sure the phase of iron carbide before and after the FTS reaction is consistent, and the phases of the used IO-350 • C and IO-450 • C catalysts were characterized by XRD (Figure 7a). It can be seen that in addition to the respective iron carbide (Fe 5 C 2 and Fe 3 C) phases, the used catalysts also have a Fe 3 O 4 phase, that is, internal oxidation occurred [30,31], which is the active phase of the WGS reaction. It can be said that the iron carbide phases of the used catalyst have been maintained almost the same as the fresh catalysts.…”
Section: Characterization Of the Used Iron Carbide Catalystsmentioning
confidence: 99%